Eating habits and behaviors of university students, Jujuy, Argentina, 2022 - Vera, Jorge Luis (2023)
Objective. Present study was to know the eating habits and behaviors of students who are studying the frist year of their degree in Nutrition, in theSan Salvador Academic Department of the Catholic University of Santiago del Estero, Jujuy, Argentina, in 2022. Methods. The research was conducted from a flexible qualitative approach and used the dietary anamnesis as an instrument for collecting information. The interviews were semi-structured, individual and virtual, with open questions to learn habits and behaviors referred to what, how much,why, what, with whom and where students usually eat. The analysis was carried out through the process of discovery, codification and relativization, considering the categories defined a priori and emergent. Results. It was possible to know the behaviors and eating habits of the students, the context of the commensality, the tastes, preferences and food aversions, as well as the complexity underlying them. Conclusions. Research on food practices should not be reduced only to the selection of foods in variety and quantity, but it is necessary to know the context and circumstances in which the food event takes place on a daily basis. It is important to know the accepted and denied tastes, preferences, aversions and dislikes, food strategies, senses, meanings, types of commensality, among other characteristics.